Exploring the link between lecturer writing assessment literacy and student learning experiences - Nia Pujiawati; Januarius Mujiyanto; Rudi Hartono; Issy Yuliasri (JEELS (Journal of English Education and Linguistics Studies), 2026)
Teachers' and students' ability to understand and apply principles of assessment, referred to as assessment literacy (AL), is central to sustaining high-quality teaching and learning. Despite growing recognition of AL's importance in L2 writing instruction, research directly measuring its impact on students' writing development remains limited. This study examines the influence of teachers’ writing assessment literacy (WAL) on students’ learning experiences in advanced L2 writing courses. Drawing on a multi-phase approach, a total of 24 teachers were first assessed using a writing assessment literacy test and then divided into proficiency groups. A total of 92 students (distributed across four groups of 18, 24, 26, and 24 participants, each corresponding to a teacher proficiency group) had their perceptions of assessment practices collected using the Assessment Experience Questionnaire and analyzed alongside the teacher groups. Surprisingly, the results showed that students of teachers with lower levels of writing assessment literacy (WAL) expressed significantly more positive views about assessment practices and educational experiences than those whose teachers had higher WAL levels. These findings challenge the prevailing assumption that greater teacher expertise inevitably leads to better student outcomes and highlight the complexity of the WAL–student learning relationship. The study highlights the need for context-sensitive approaches to professional development and suggests that both standardized and differentiated assessment strategies can provide significant benefits for diverse learners.